Perceptions of failed mathematics education students toward preparatory mathematics course - Simamora, Rustam Effendy; Tanjung, Firima Zona; Rizmawati, Lusiana; Lastari, Dini Adhe (Universitas Papua, 2024)
Investigating the experiences of mathematics education students who have faced academic challenges is vital for shaping the professional development of future mathematics educators. This study examines the experiences of Indonesian mathematics education students who have encountered difficulties in a Preparatory Mathematics Course (PMC). Employing a qualitative case study narrative approach, we explore these students’ perceptions, emphasizing the crucial role of foundational mathematics skills and the potential of PMC in aiding underprepared learners. Data were collected through questionnaires and interviews. The findings reveal varied perspectives on the course's value. Some students recognized its significance and contribution to their university studies, particularly in mathematics content courses, while others viewed it as less impactful. Factors contributing to student failures included a lack of focus and dedication, carelessness in test assessments, and discrepancies between expected and actual learning experiences. Additionally, participants provided constructive suggestions for improving the course, such as integrating collaborative learning, enhancing assignments and assessments, incorporating instructional videos, offering in-person learning opportunities, adjusting schedules, and facilitating anonymous online discussion forums. These insights offer valuable directions for refining PMC and improving outcomes for mathematics students and educators.